2016
DOI: 10.25159/2520-5293/1491
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Religion in the Uptake of Male Circumcision as an Hiv Prevention Strategy in Swaziland

Abstract: Circumcision has been practised for centuries among various groups of people world-wide, mainly for religious, traditional, hygienic or medical reasons. However, this practice was rare in Swaziland. Following recommendations by the World Health Organisation that circumcision should be added as an additional strategy for HIV prevention, the country embarked on mass male circumcision campaigns, aimed at scaling up the practice nationwide. Apparently the turnup for the procedure is below the set targets. Knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(2 reference statements)
2
0
0
Order By: Relevance
“…Similar findings emerged from Maibvise and Mavundla’s 31 study on medical reasons for performing adult male circumcision in Swaziland, which indicated that some men get circumcised not because they want to do so, but as a treatment for phimosis and paraphimosis.…”
Section: Resultssupporting
confidence: 71%
“…Similar findings emerged from Maibvise and Mavundla’s 31 study on medical reasons for performing adult male circumcision in Swaziland, which indicated that some men get circumcised not because they want to do so, but as a treatment for phimosis and paraphimosis.…”
Section: Resultssupporting
confidence: 71%
“…Findings revealed that all Muslims contributing 7.5% of the total respondents who were interviewed in the study were already circumcised while the number of circumcised respondents who belonged to other religions varied that is; Anglican/Protestants (45%), Catholics (33.33%), Pentecostal church (11.67%) and Seventh Day Adventists (2.5%). This agrees with results from a study conducted in Swaziland on the influence of religion on the uptake of male circumcision, the findings revealed that religion has both negative and positive influences on individual perception and hence the decision to get circumcised C. Maibvise, (2015). This is probably because for Muslims it's mandatory for every individual in the religion to get circumcised to be regarded as a true Muslim and other religions do not take it as a very serious issue, however, the study area is ma-jorly composed of Anglican/Protestants followed by catholic religion.…”
Section: Assessment Of Factors Affecting Utilization Of Safe Male Cir...supporting
confidence: 90%